The first specimen of Deinotherium indicum (Mammalia, Proboscidea, Deinotheriidae) from the late Miocene of Kutch, India. (July 2020) - Singh, Ningthoujam Premjit; Jukar, Advait M.; Patnaik, Rajeev; Sharma, K. Milankumar; Singh, Nongmaithem Amardas; Singh, Yumlembam Priyananda
Abstract: Deinotheriidae Bonaparte, 1845 is a family of browsing proboscideans that were widespread in the Old World during the Neogene. From Miocene deposits in the Indian subcontinent, deinotheres are known largely from dental remains. Both large and small species have been described from the region. Previously, only small deinothere species have been identified from Kutch in western India. In the fossiliferous Tapar beds in Kutch, dental remains have been referred to the small species Deinotherium sindiense Lydekker, 1880, but the specimens are too fragmentary to be systematically diagnostic. Here, we describe a large p4 of a deinothere from the Tapar beds and demonstrate that it is morphologically most similar to Deinotherium indicum Falconer, 1845, a large species of deinothere, thereby confirming the identity of deinotheres at Tapar. Deinotherium indicum from Tapar is larger than other deinotheres identified from Kutch and is the first occurrence of the species in the region. This new specimen helps constrain the age of the Tapar beds to the Tortonian and increases the biogeographic range of this species—hitherto only known from two localities on the subcontinent. This specimen also highlights the morphological diversity of South Asian deinothere p4s and allows us to reassess dental apomorphies used to delimit Indian deinothere species. Lastly, we argue that by the late Miocene, small deinotheres in Kutch were replaced by the large Deinotherium indicum .